Investigating a key structural determinant of health, racism, and related social determinants of health in Massachusetts during the COVID-19 pandemic - Mortimer, Arvis E.; Sabatino, Meagan J.; Boama-Nyarko, Esther; Castañeda-Avila, Maira; Goulding, Melissa; Julce, Clevanne; Labossiere, Stephane; Mabry, Guadalupe; McCullers, Asli; McNicholas, Eileen; Moormann, Ann; Schieber, Elizabeth; et al. (Frontiers in Epidemiology, 2022)
A disproportionate burden of the ongoing COVID-19 pandemic is being shouldered by members of racial and ethnic minorities and socially disadvantaged communities. Structural and social determinants of health have been recognized as key contributors to the inequalities observed. Racism, a major structural determinant of health that patterns related social determinants of health, in the USA, warrants further investigation. In this perspective piece we provide an overview of the historical context of racism, followed by preliminary findings from the ongoing COVIDStory study – a cross-sectional study addressing perceptions of COVID-19 and COVID-19 research – that highlights the experiences of non-Hispanic Black and Hispanic identifying adult participants, residing in Worcester Massachusetts, during the COVID-19 pandemic. We then discuss these findings in the context of current and past research considering racism and relevant social determinants of health. Our study results suggest that racism and its residuals (residential segregation, economic insecurity, discrimination, bias, and vigilance) are modern challenges for non-Hispanic Black and Hispanic participants, and these findings are supported by the existing literature. It is our hope that this perspective piece provides additional evidence for action on structural and social determinants affecting the health of minoritized people, especially those living in Massachusetts.